Native bamboos with invasive traits: impacts, consequences and challenges with special emphasis on Asia Pacific Region - S. Madawala; T. Wijewickrama (Ceylon Journal of Science, 2021)
Defying all norms of biological invasions, some native species expand their populations similar to their exotic counterparts causing potentially harmful impacts in native habitats. Despite an early caution by ecologists, they are now recognized as ‘native invaders’. Though ‘native’ invaders may also incur harmful impacts similar to their ‘exotic’ counterparts, there are clear contrasts between them, thus demanding further studies to explore their life traits and cues that trigger their invasive traits. Among native invaders, bamboos are in the forefront due to their robust growth and resilience to harsh conditions. Also, it is a known fact that bamboo-dominated forests are on the increase globally while native forest are declining at a rapid rate. This review attempts to condense the current understanding of ‘native’ bamboos that spread in the Asia Pacific region with invasive potential and their short- and long-term ecological impacts. Possible environmental cues that may trigger their ‘invasive’ nature are also discussed. Of many, climate change seems to be the major driving force triggering their invasive behavior, though long-term studies are needed to ratify this link. Major challenges and knowledge gaps that hamper their control have also been deliberated. The evidence confirmed that native bamboos have the potential to incur negative impacts on ecology, social and economic aspects. However, their impacts are not always in parallel with that of ‘exotic’ invaders, thus cautioning any attempt of generalization. The lack of comprehensive research and historical information are considered as major impediments to identify suitable measures to manage them effectively. Further studies are mandatory to fill the existing knowledge gaps and to identify challenges to bring about effective management strategies to control ‘native’ bamboos with invasive potential.